2
$\begingroup$

Question -

Find all $f: \mathbb{N} \rightarrow \mathbb{N}$ which satisfy the relation -

$$ f(m-n+f(n))=f(m)+f(n) $$ for all $m, n \in \mathbb{N}$ where $N={1,2,3....}$

solution -

Observe $f(n) \geq n .$ Consider $F(n)=f(n)-n .$ Show that $F$ satisfies $$ F(F(n)+m)=F(m)+n $$ Using this, conclude that $F(1)=1$

and $F(n+1)=F(n)+$ $F(1)$ for all $n \geq 1 .$ Thus $F(n)=n F(1) .$ It follows that $F(n)=n$ and $f(n)=2 n$

Now i did not understand how they proved $F(1)=1$ ???

Any help will be appreciated

thankyou

$\endgroup$
1
  • $\begingroup$ Is this function well defined? How do you know that $$m-n+f(n)>0$$ is true for all $m$ and $n$? $\endgroup$ Apr 22, 2020 at 10:12

4 Answers 4

1
$\begingroup$

I don't understand how he proved it, but here's my solution: $$f(m-n+f(n))=f(m)+f(n) \implies P(m,n)$$ $$P(0,0) \implies f(f(0))=2f(0)$$ Let $f(0)=c$ giving $f(c)=2c$, so $$P(m,c)\implies f(m+c)=f(m)+2c $$ $$P(m,0) \implies f(m+c)=f(m)+c $$ So, $c=2c \implies c=0 \implies f(0)=0$ $$P(n,n) \implies f(f(n))=2f(n)$$ Let $f(1)=k$ $$P(1,1) \implies f(k)=2k$$ $$P(m,1) \implies f(m-1+k)=f(m)+k$$ $$P(m-1,k) \implies f(m-1-k+2k)=f(m-1+k)=f(m-1)+2k$$ So, combining the previous 2 equations, we get $$f(m)+k=f(m-1)+2k \Leftrightarrow f(m)-f(m-1)=k \implies H(m) $$ $$H(2)\implies f(2)-f(1)=k \implies f(2)=2k$$ $$H(3)\implies f(3)-f(2)=k \implies f(3)=k+f(2)=k+2k=3k$$ and so on, by simple induction, and the fact that $f(0)=0$ $$f(x)=kx \text{ } \forall \text{ } x \in \mathbb{N}$$ Substituting in the original equation, $$km-kn+{k^2}n=km+kn \Leftrightarrow {k^2}n=2kn \Leftrightarrow k^2=2k \Leftrightarrow k^2-2k=0 $$ $$ \Leftrightarrow k(k-2)=0$$ This gives $$(1) \text{ } k=0 \implies f(x)=0 \text{ } \forall \text{ } x \in \mathbb{N}$$ $$(2) \text{ } k=2 \implies f(x)=2x \text{ } \forall \text{ } x \in \mathbb{N}$$ the only 2 solutions $\Box$.

Note that when $0$ doesn't belong to $\mathbb{N}$, you can discard all the steps of relating to $0$ and the proof would still hold true.

$\endgroup$
2
  • $\begingroup$ i have clearly mention in question that N=1,2,3.....!!! $\endgroup$
    – Ishan
    Apr 22, 2020 at 3:19
  • 1
    $\begingroup$ @User88463 I edited that: note that you can discard all the steps relating to zero and the proof would still hold true for $f(x)=2x$ only $\endgroup$ Apr 22, 2020 at 23:26
0
$\begingroup$

$f(0)+f(0)=f(f(0))$

$f(0)+f(f(0))=f\bigg(0-f(0)+f(f(0))\bigg)=f\bigg(0-f(0)+f(0)+f(0)\bigg)=f(f(0))$

Subtracting $f(f(0))$ each side we get $f(0)=0$

$f(0)+f(n)=f(n)=f(0-n+f(n))\iff f(n)=f(f(n)-n)$

$f(m)+f(n)=f(m)+f(f(n)-n)=f\bigg(m-f(n)+n+f(f(n)-n)\bigg)=f\bigg(m-f(n)+n+f(n)\bigg)=f(m+n)$

Thus $f$ is linear with $f(0)=0$ so $f(n)=an$.

Reporting in equation $f(n)+f(n)=f(f(n))\iff 2an=a^2n\iff a=2, a=0$

Thus $f(n)=2n$ or $f(n)=0$

$\endgroup$
1
  • $\begingroup$ but N does not contain 0 !!! $\endgroup$
    – Ishan
    Apr 20, 2020 at 12:17
0
$\begingroup$

I cannot comment, so I will do it here for @zwim: you are using the functional equation for m negative (in $f(0)+f(n)=f(n)=f(0-n+f(n))\iff f(n)=f(f(n)-n)$)

My solution: Let us consider $h(n) = f(n) - 2n$. $h$ verify the functional equation: $$h(m+n+h(n)) = h(m) - h(n), \text{ where } h: \mathbb{N}_{>0} \to \mathbb{Z}$$ we extend $h$ to $\mathbb{N}$ by $h(0) = 0$. In particular we have: $h(2n + h(n)) = 0$. So if there exists $n_0 > 0$ s.t. $h(n_0) = 0$, we have $h(m + n_0) = h(m)$ so $h$ is $n_0$-periodic. Let $0 < i < n_0$, we put $h_i = h(i)$. We have $$h(n+i+h_i) = h(n) - h_i$$ and by induction: $$h(n+k(i+h_i)) = h(n) - kh_i$$. By choosing $k = n_0$, we conclude $h_i = 0$, so by periodicity we have $h(n) = 0$, so $f(n) = 2n$. Otherwise, if there isn't $n_0>0$ s.t. $h(n_0) = 0$, then from $h(2n+h(n)) = 0$ we conclude $f(n) = 0$.

$\endgroup$
2
  • $\begingroup$ $h$ is from $\mathbb{N} \to \mathbb{Z}$. If you exclude $0$ from $\mathbb{N}$ (which is $\mathbb{N}_{>0}$) then the only solution is $f(n) = 2n$ $\endgroup$
    – ne3886
    Apr 20, 2020 at 14:47
  • $\begingroup$ ok, but can you pls tell me how F(1)=1 in my original doubt that actually i have....i just wanted to know that how they write $F(1)=1$ after substituting $F(n)=f(n)-n$ ? if this doubt will be cleared then i have very easy solution for this problem... $\endgroup$
    – Ishan
    Apr 20, 2020 at 15:39
-1
$\begingroup$

let $F(n) = f(n) - n$. $F$ verify the functional equation: $$F(m + F(n)) = F(m) + n$$ By choosing $m=0$, we have $F(F(n)) = F(0) + n$, so $F$ is injective. By letting $n=0$, we have $F(m+F(0)) = F(m)$ and by injectivity we deduce $F(0) = 0$. Now we have $F(F(n)) = n$ so now $F$ is surjective. Let $n_0$ s.t. $F(n_0) = 1$. We have now: $$F(m + 1) = F(m) + n_0$$ so: $$F(m) = n_0 m$$ by inserting this into last equation we deduce $n_0^2 = 1$ so $n_0 = 1$. I have prouved $F(1) = 1$. Now by induction we deduce $F(n) = n$, i.e. $f(n) = 2n$

$\endgroup$
1
  • $\begingroup$ are you serious ??? i have told many time in this post that N=1,2,3.... $\endgroup$
    – Ishan
    Apr 23, 2020 at 15:51

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.